MEDIA FLASHCARD BRAILLE TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK TUNANETRA - Khairani, Mutia (Jurnal Pendidikan Khusus, 2016)
Abstract Based on the observation result in SLB-A YPAB Tegalsari Surabaya, the blind children of class I had hindrance in beginning reading Braille including recognizing alphabets, vocabulary, and Braille words. To enhance the ability in beginning reading it was given the application of Braille flashcard media. This research had purpose to analyze whether there was influence of using flashcard media in blind children’s learning in SLB-A YPAB Tegalsari Surabaya or not. The approach used in this research was quantitative approach. The kind of research used was pre experiment. The design used was: the one group pretest and posttest. For the data analysis this research used the analysis technique of statistic non parametric. The research result after giving pretest was that the average value of blind children was 34 and then it was given intervention 6 times with ± 60 minutes of time allocation for each meeting. Then it was given posttest and the result indicated that the change happened, the children’s value was better with the average value 82,5. From the value above it was then analyzed using sign test formula (ZH) with Z table 5% of one side test 1,96. The Z value obtained in counting was ZH = 2,05 so that it could be concluded that “there was significant influence to beginning reading ability of blind children” with ZH value = 2,05 > Z table 5% 1,96. Keywords: Flashcard, Braille, ginning reading